2011
DOI: 10.1134/s0006297911040110
|View full text |Cite
|
Sign up to set email alerts
|

Cyanines as efficient photosensitizers in photodynamic reaction: Photophysical properties and in vitro photodynamic activity

Abstract: The purpose of the present study was to explore the potential application of cyanines in photodynamic treatment. The photophysical features of four cyanines (KF570, HM118, FBF-749, and ER-139) were investigated by elemental and spectral analyses. Two malignant cell lines (MCF-7/WT and MCF-7/DOX) were used to test the potential for use in the photodynamic therapy. The cytotoxic effects of these dyes were determined by the MTT assay after 4 and 24 h of incubation with the cyanine. KF570 and HM118 were irradiated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…As it has been proved in our previous study (Kulbacka et al, 2011;Pietkiewicz et al, 2010) doxorubicin-resistant variant (MCF-7/DOX) demonstrated a significantly lower accumulation of cyanine-type photosensitizers. The drugloaded nanoparticles were found to access the interior of the tumor cells, followed by an appreciable drug release inside as a result of the cancer cellular uptake of nanocarriers by means of diffusion or phagocytosis/endocytosis mechanisms (Müller et al, 2001).…”
Section: Uptake Of Multilayer Nanocapsules By Tumor Cellsmentioning
confidence: 72%
See 3 more Smart Citations
“…As it has been proved in our previous study (Kulbacka et al, 2011;Pietkiewicz et al, 2010) doxorubicin-resistant variant (MCF-7/DOX) demonstrated a significantly lower accumulation of cyanine-type photosensitizers. The drugloaded nanoparticles were found to access the interior of the tumor cells, followed by an appreciable drug release inside as a result of the cancer cellular uptake of nanocarriers by means of diffusion or phagocytosis/endocytosis mechanisms (Müller et al, 2001).…”
Section: Uptake Of Multilayer Nanocapsules By Tumor Cellsmentioning
confidence: 72%
“…The concentration of IR-786 in all experiments with loaded nanocarriers was adjusted to be the same as that of the free dye molecules, i.e., 4 Â 10 À6 M. Control cells (negative control without cyanine IR-786 or with empty nanocapsules) were processed in the same way. The experiment conditions (amount of light/drug doses and time of exposure of the cells) were set similar to our earlier studies (Kulbacka et al, 2011;Pietkiewicz et al, 2010) as well as to literature data describing cyanine-type photosensitizers and other photosensitizing agents, (Delaey et al, 2000;Usuda et al, 2003;Zhao et al, 2009) in order to prove that the dose and light exposure conditions that were applied to the IR -786 encapsulated form is enough efficient in relation to the native photosensitizer. The cells were irradiated for 10 min with a total light dose of 6 J/cm 2 using a lamp (OPTEL Opole, Fibre Illuminator, Poland) with polarized light and a infrared-pass filter (k max 760-800 nm).…”
Section: Assay Of In Vitro Photo-induced Anticancer Effectsmentioning
confidence: 98%
See 2 more Smart Citations
“…The cyanine derivatives, a complex group of dyes containing numerous subgroups featuring cationic and anionic compounds, appear to have interesting properties and they have been studied as potential PDT dyes in recent years. Some authors have reported on application of indocyanine green, squarylium cyanine and MC540 in photodynamic therapy (8,9). Such structures were used for the selective…”
Section: Introductionmentioning
confidence: 99%